Reflections on Human-Nature Relations: A Critical Review in Islamic Humanities - Karimullah, Suud Sarim (Jurnal Adabiyah, 2023)
The relationship between humans and nature are two things that cannot be separated. Even though humans have a responsibility to maintain the environment, humans often also become the source of environmental problems.This study aims to delineate the understanding of the concept of humanity in Islam and its relationship with the environment, highlighting critiques directed at human practices related to the environment and exploring efforts to align beliefs and environmental sustainability through the lens of Islamic humanities. A holistic method of literary analysis is employed in this study, involving an exploration of relevant sources, including religious texts and scholarly literature in Islamic humanities. The findings of this study underscore that the Islamic concept of humans as stewards of the universe forms the foundation of environmental ethics. However, human actions often fail to reflect this role, resulting in adverse impacts such as pollution, resource exploitation and climate change on the environment. In the context of changing times and global environmental challenges, environmental ethics in Islam remains a subject of ongoing debate. Therefore, it is essential to replace outdated understandings with more diverse interpretations within Islamic humanities and to regard Islamic values concerning the environment as valuable intellectual assets open to continuous debate. Through a holistic approach, Islamic humanities can serve as an educational tool, a source of inspiration and a driver of ethical actions toward the environment in Muslim communities and across the broader human society. الملخص تهدف هذه الدراسة إلى تحديد فهم مفهوم الإنسانية في الإسلام وعلاقتها بالبيئة ، وتسليط الضوء على الانتقادات الموجهة للممارسات الإنسانية المتعلقة بالبيئة واستكشاف الجهود المبذولة لمواءمة المعتقدات والاستدامة البيئية من خلال عدسة العلوم الإنسانية الإسلامية. يتم استخدام طريقة شاملة للتحليل الأدبي في هذه الدراسة ، والتي تنطوي على استكشاف المصادر ذات الصلة ، بما في ذلك النصوص الدينية والأدب العلمي في العلوم الإنسانية الإسلامية. تؤكد نتائج هذه الدراسة على أن المفهوم الإسلامي للإنسان كحكام للكون يشكل أساس الأخلاق البيئية. ومع ذلك ، غالبا ما تفشل الإجراءات البشرية في عكس هذا الدور ، مما يؤدي إلى آثار ضارة مثل التلوث واستغلال الموارد وتغير المناخ على البيئة. في سياق الأزمنة المتغيرة والتحديات البيئية العالمية ، تظل الأخلاق البيئية في الإسلام موضوع نقاش مستمر. لذلك ، من الضروري استبدال التفاهمات التي عفا عليها الزمن بتفسيرات أكثر تنوعا في العلوم الإنسانية الإسلامية والنظر إلى القيم الإسلامية المتعلقة بالبيئة كأصول فكرية قيمة مفتوحة للنقاش المستمر. من خلال نهج شامل ، يمكن أن تكون العلوم الإنسانية الإسلامية بمثابة أداة تعليمية ، ومصدر إلهام ، ومحركا للإجراءات الأخلاقية تجاه البيئة في المجتمعات الإسلامية وعبر المجتمع البشري الأوسع. الكلمات المفتاحية: العلاقات بين الإنسان والطبيعة ، العلوم الإنسانية الإسلامية ، الأخلاق البيئية Abstrak Hubungan manusia dan alam adalah dual hal yang tak dapat dipisahkan. Meskipun manusia memiliki tanggung jawab dalam pemeliharaan lingkungan tetapi manusia sering juga menjadi sumber masalah lingkungan. Kajian ini bertujuan untuk menggambarkan pemahaman konsep manusia dalam Islam serta relasinya dengan alam, menyoroti kritik yang ditujukan pada praktik manusia terkait alam, dan menjelajahi upaya untuk menyelaraskan keyakinan dan keberlanjutan alam melalui pendekatan Islamic humanities. Metode analisis literatur yang holistik digunakan dalam kajian ini dengan eksplorasi sumber-sumber yang relevan, termasuk teks agama dan literatur ilmiah dalam Islamic humanities. Hasil kajian ini menyoroti bahwa konsep manusia dalam Islam sebagai khalifah yang bertanggung jawab terhadap alam semesta membentuk dasar etika lingkungan. Namun, seringkali tindakan manusia tidak mencerminkan peran tersebut, menyebabkan dampak negatif seperti polusi, eksploitasi sumber daya, dan perubahan iklim pada alam. Dalam konteks perubahan zaman dan tantangan lingkungan global, etika lingkungan dalam Islam menjadi subjek perdebatan yang terus berlanjut. Oleh karena itu, penting untuk menggantikan pemahaman lama dengan interpretasi yang lebih beragam dalam Islamic humanities dan menjadikan nilai-nilai Islam tentang lingkungan sebagai aset intelektual yang bernilai untuk terus diperdebatkan. Melalui pendekatan holistik, Islamic humanities dapat menjadi alat pendidikan, sumber inspirasi, dan pendorong tindakan etis terhadap alam dalam masyarakat Muslim dan seluruh umat manusia. Kata Kunci: Relasi Manusia-Alam; Humaniora Islam; Etika Lingkungan